(untitled) (The International Journal for Scientific Research, 2025)
Families of disjoint sets colouring (partitioning) technique is trial to unify and generalize all types of colouring such as edge colouring, vertex colouring, and face colouring. The concept of standard of partitioning edges into colour classes is essential concept to follow and understand families of disjoint sets colouring (partitioning) technique. In this paper, we introduce some examples of standard of partitioning, and introduce some results of partitioning edges. Some of these results explain importance of standard of partitioning related to subgraphs, and some results related to maximum number of edges belongs to each colour class. Also, we introduce results of partitioning edges related to quasi non common edges. Here we list some properties related to standard of partitioning edges into colour classes.